Analisis Prosedur Penjualan Kredit Motor Pada PT. Adira Finance Cabang Kota Dumai - Fitria, Lailani; Indah, Debora; Danisa, Tengku (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2025)
ABSTRACTProcedures is a series of organized and systematic steps or actions that must be followed to achieve a goal or complete a task. Procedures are usually established to ensure consistency, efficiency, and safety in carrying out certain activities or processes. Starting from creating proof of the transactions carried out, then checking and waiting for approval. The aim of this research is to analyze the procedure for selling motorbikes on credit, and the object of this research is PT. Adira Finance Dumai Branch, and data collection was carried out by direct interviews with one of the sales marketing employees of PT. Adira Finance Cabang Dumai. The data that has been taken is analyzed using qualitative methods by describing conditions and events and the results obtained are in the form of field interview data. The results of this research show that the procedures have been neatly arranged so that interested customers do not have difficulty understanding the flow of motorbike sales on credit through the use of a flowchart. Keyword: sales procedures, credit, flowchart, accounting information system